ORGANIZING INVESTMENT PROJECTS EFFICIENCY ASSESSMENT AND MONITORING (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The function and economic content of investment. Investments are the introduction of long-term funds for the purpose of creating new production enterprises or modernizing existing enterprises, mastering advanced techniques and technologies, increasing product production and profit (income) at the scale of the economy and enterprises. Investments have a special focus on improving the structure of social production, eliminating imbalances in production and ensuring the consumer market.